Dinamika Komposisi pada Sistem Tangki Pencampur 10 Liter - Yulius Deddy Hermawan (Seminar Nasional Teknik Kimia Kejuangan, 2012)
The liquid concentration dynamic behavior of a 10 L mixing tank has been studied experimentally. Tank with volume of 10 liter are designed and arranged for experimentation in laboratory. The tank has two input streams, stream-1 is the water-stream with its volumetric rate of f1 [cm3/sec] and stream-2 is salt solution with its volumetric rate of f2 [cm3/sec] and salt composition of c2 [gr/cm3]. Since the tank is designed overflow, the liquid volume in tank is always constant. In this work, the mass disturbance load has been made based on step increase and decrease. Those disturbance include the changes of the flow-rate input (f1 and f2) and the concentration of the input stream (c2). The dynamic behavior of mixing tank system has also been explored. As can be seen from our investigation in laboratory,the mixing tank with volume capacity of 10 liter produces a stable responce. Furhtermore, the open loop dynamic simulation using computer programing is also done, and its simulation result are compared with the experiment data from laboratory. The developed mathematical model of the mixing tank system has been solved analytically by laplace transform. The trends of simulation results are quite similar with those in our experiment results.